Effects of Injection of Carbon Nanotubes on EEG and Results of a Behavioral Test in Rats - Azimirad, V.; Hosseinpour, M.; Shahabi, P.; Alimohammadi, M.; Sadighi, M.; Hatami, H. (Нейрофизиология, 2015)
We examined the biocompatibility of carbon nanotubes (CNTs) injected i.p. into rats (1 mg/kg
body mass) by recording EEG from the frontal and occipital cortex and performing the
water maze router test before and after such injection. For EEG, the energy and average
power spectral density of wavelet coefficients in the β, α, and θ bands were considered the
features. In the water maze router experiment, the distance, time, and speed of rats were
investigated as behavioral factors. Comparison of EEG signals before and after injection
showed that introduction of CNTs exerted no significant effect on electrophysiological brain
indices. A comparison of behavioral factors before and after injection, however, showed that
injections of CNTs increased the pacing distance and time to find the desired platform and
decreased somewhat the speed in the water maze router experiment. A possible reason of this
phenomenon is the possible influence of CNTs on ion fluxes in brain neurons. Ми досліджували біосумісність вуглецевих нанотрубок
(ВНТ), ін’єкованих щурам (1 мг/кг маси тіла, внутрішньоочеревинно), відводячи ЕЕГ та застосовуючи поведінковий
тест із водним лабіринтом перед такою ін’єкцією та після
неї. Параметрами ЕЕГ вважали енергію та усереднені щільності спектральної потужності вейвлет-коефіцієнтів для
бета-, тета- та альфа-ритмів. В експерименті з водним лабіринтом поведінковими факторами були відстань, час та
швидкість руху щурів у пошуках цільової платформи. Порівняння сигналів ЕЕГ перед ін’єкцією ВНТ та після неї
показало, що введення нанотрубок істотно не впливало на
електрофізіологічні показники мозку. Порівняння ж поведінкових показників перед ін’єкцією та після неї, проте, засвідчило, що введення ВНТ викликало вірогідне збільшення
шляху до платформи і тривалості її пошуків, а також деяке зменшення швидкості пересування у водному лабіринті. Можливою причиною такого феномену є вплив ВНТ на
іонні токи в нейронах мозку.